Fungsi Tari Dugder Denok Kenang dalam Budaya Semarang - Rachmad Grihasta Yoga Pratama; Usrek Tani Utina (Dinasti Research, 2026)
This study aims to analyze the function of the Dugder Denok Kenang Dance in the cultural context of Semarang City. Created in 2021, the dance highlights the Dugderan tradition as a representation of Semarang’s cultural identity. This study uses a qualitative method with an ethnographic approach. Data were collected through observations at Sanggar Anugerah Berkah Langgeng (ABL Studio), in-depth interviews with choreographers, dancers, and related parties, and documentation. Data were analyzed through data reduction, data presentation, and conclusion drawing. The results show four main functions of the Dugder Denok Kenang Dance: (1) social function as a medium for strengthening community relations; (2) educational function as a means of transmitting local cultural values to younger generations; (3) aesthetic function as artistic expression representing Semarang’s urban culture; and (4) identity function as a cultural symbol supporting Semarang City’s city branding. These findings indicate that the Dugder Denok Kenang Dance functions not only as a performing art but also as a medium for cultural preservation, education, social interaction, and strengthening local identity. It contributes to maintaining and promoting Semarang’s cultural heritage amid contemporary cultural development.